Pemanfaatan Media Flash Card pada Pembelajaran Mufradat Kelas VII Madrasah Tsanawiyah Ma’had Al-Zaytun Tahun 2024 - Ilma Nasiroh; Irvan Iswandi; Moch. Hasyim Fanirin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
In the learning process, learning media is needed so that the learning process is not monotonous and boring. Flash card media is one of the many media used in the Arabic language learning process, especially in learning mufradat. This research examines the utilization of flash card media in learning mufradat class VII Madrasah Tsanawiyah Ma'had Al-Zaytun in 2024. The focus of the problem of this research is how the utilization of flash card media and what is the impact of using flash card media on learning mufradat class VII Madrasah Tsanawiyah Ma'had Al-Zaytun. The purpose of this research is to find out the utilization of flash card media and the impact of using flash card media on learning mufradat class VII Madrasah Tsanawiyah Ma'had Al-Zaytun. This research used qualitative method. Data were collected through observation, in-depth interviews with students and Arabic teachers of grade VII, documentation and questionnaires. The samples taken were class VII-A-07 which amounted to 28 students and VII-B-02 which amounted to 26 students. Sampling using purposive sampling technique. The results of this study showed that the use of flash card media in learning mufradat in class VII of Madrasah Tsanawiyah Ma'had Al-Zaytun in 2024 showed positive results. Flash card media as learning media is able to increase student motivation and interest, create a more relaxed and active learning atmosphere, improve understanding and memory, increase student focus, and overcome learning difficulties